PENGARUH ACARA PARIWISATA OLAHRAGA, CITRA DESTINASI HALAL, DAN NILAI YANG DIRASAKAN TERHADAP NIAT BERPERILAKU WISATAWAN UNTUK BERKUNJUNG KEMBALI, MEREKOMENDASIKAN KEPADA ORANG LAIN DAN POSITIF WOM - Baiq Nadia Nirwana; Sulhaini Sulhaini; Lalu Edy Herman Mulyono (Master of Management, Mataram University, 2020)
This study aims to examinethe influence of sport tourism events, halal destination image, and perceived value on behavioral intentions of tourists at the Mandalika International Marathon event. Data collection was carried out among both active and passive participants of the Mandalika International Marathon by using the associative quantitative method. Furthermore, the data collected was analyzed further. This study uses structural equation modeling analysis (SEM analysis) with AMOS applications. The results of the study indicated that sport tourism events haves a significant positive effect on behavioral intentions, and the halal destination image has a significant positive effect on perceived value. The West Nusa Tenggara government is supported event organizers to develop halal tourism and sport tourism events. This is to enhance, halal destination image in NTB is not only for religious tourism.Keywords :Event Sport Tourism, Halal Destination Image, Perceived Value, Behavioral Intentions.